TOURIST VILLAGE DEVELOPMENT THROUGH COMMUNITY EMPOWERMENT APPROACH - suryaningprang, andre; Herlina, Listri; Wiryany, Detya; Nuradina, Kartika (LPM Universitas Pasundan, 2023)
The tourist area is a tourism asset of an area that must be maintained and developed with all its attractiveness and uniqueness. Tourist visits to a place depend on the advantages possessed by the area. Tourism villages certainly have an effect on the economy of an individual, community to a region. In the Law of the Republic of Indonesia Number 10 of 2009, tourism is a variety of tourism activities and is supported by various facilities and services provided by the community, businessmen, government and local governments. In addition, in law number 20 of 2009 concerning tourism which states that the condition of nature, flora and fauna as a gift from God Almighty, as well as historical, artistic